Medicinal plants for gallstones: A cross-sectional survey of Moroccan patients - Asma Arrout; Yassine El Ghallab; Mohamed Yafout; Mohammed Rachid Lefriyekh; Amal Ait Haj Said (Elsevier, 2024)
Background: Gallstone is an expensive and very common gastrointestinal disorder affecting 10-20 % of the adult population. The traditional use of medicinal plants in Morocco is an ancestral and common practice to solve health problems, including gallstone disease. Our study aimed to identify the medicinal plants used by patients suffering from gallstones. Methods: A cross-sectional survey was conducted on the use of medicinal plants for the treatment of gallstones in the visceral surgery department, University Hospital Center Ibn Rochd of Casablanca, Morocco. Face to face interviews were carried out with 128 hospitalized patients using a closed-ended questionnaire. Results: Patients with gallstones underlined the use of 35 species belonging to 21 botanical families. The most frequently used plant was Citrus limon, followed by Petroselinum sativum, Herniaria hirsuta and Olea Europea, belonging respectively to Rutaceae, Apiaceae, Caryophyllaceae and Oleaceae. The respondents used different parts of plants; seeds, aerial parts, fruits and leaves. The most commonly preparations were decoction, infusion and powder form. More than two-thirds of the patients were overweight or obese, regularly consume soft drinks and drink little water a day. Conclusion: The pharmacological effect of the inventoried plants and their active ingredients are consistent with their use in the traditional Moroccan pharmacopoeia to treat and to prevent gallstones. These plant species could be a potential avenue for the discovery of an alternative treatment; however, further chemical and pharmacological investigations are needed.